Study guide and workbook for use with Foundations of financial management - Block, Stanley B (McGraw-Hill Irwin, 2002)
This text for students on financial management considers contemporary issues featuring companies such as Netscape and America Online. The work contains examples and problems which require the application of several financial concepts.